Good Corporate Governance Menghasilkan Laporan Keuangan Berkualitas dan Pengaruhnya Terhadap Kinerja Keuangan - Arna Suryani; Elia Rossa (Universitas Batanghari Jambi, 2020)
This research aims at finding out and analyzing how good corporate governance produces financial statement which has a certain quality that affects the company's financial performance. The population of this research is a sub-sector of the property listed on the Indonesia Stock Exchange period of 2014-2018, with the selection of samples based on the selected purposive sampling of 16 companies. The data was analyzed by using multiple linear regression by conducting classical assumption tests and hypothesis tests. The results of the research show that good corporate governance measured with the commissioner, foreign ownership and audit committees are simultaneously and significantly affect the financial performance measured by return on asset. Partially the Board of Commissioners have a significant effect on financial performance with a substantial of 1.299. Foreign ownership and audit committees have no significant effect on the financial performance in which the value of sig is > 0.05. The value of coefficient of determination of R2 amounted to 72.9% showed that Return On Asset variation can be explained by the variation of Board of Commissioners, foreign ownership and audit committee and the remain is 27.1% which is explained by other factors that do not exist in this research. The results of this research proved that the most dominant variable which has significant effect to the financial performance is the Board of Commissioners. This should be a consideration for the company in the election or designation of the Board of Commissioners to improve implementation of good corporate governance principles in order to improve the company's financial performance.